Influence of processing on nutritional and microbiological quality of maize and millet composite flours enriched with house crickets (Acheta domesticus) - Tom Bbosa; Dorothy Nakimbugwe; Christophe Matthys; Dries Vandeweyer; Tara Grauwet; Mik Van Der Borght (Applied Food Research)
Thin cereal porridges, characterized by low mineral and vitamin content per calorie, are commonly consumed as complementary and weaning foods in sub-Saharan Africa. Their nutrient-density and bioavailability could be improved by nutritious ingredients such as crickets (Acheta domesticus) and extrusion processing. However, cricket inclusion forms and appropriate processing conditions are under-studied. Cricket-enriched composite cereal flours were formulated, extruded and analyzed for nutritional and microbial characteristics. Two formulations (66.7% maize, 25.0% millet, 8.3% undried crickets and 66.7% maize, 29.2% millet, 4.2% dried crickets) were prepared. Each formulation was divided into three portions which were extruded at 120, 140 or 160 °C. A control product (73.0 % maize and 27.0 % millet) was also processed for comparison. Significant nutrient (on dry matter basis) and microbiological differences were observed with increasing extrusion temperature, cricket inclusion forms and flour batches: protein and chitin content increased more at higher extrusion temperatures in flour with dried crickets than in flour with undried crickets with negligible effects for other nutrients. The flour containing undried crickets had lower carbohydrate content than the control, minimally higher crude protein, ash, lysine, and valine content and showed significantly higher vitamin B12. Overall, zinc and iron solubilities were the same at different pH levels in flour containing undried crickets and the control. The flour containing undried crickets had lower B. cereus, total aerobic and, endospore counts than that containing dried crickets. Eliminating the cricket drying step will reduce processing time and energy expenditure without compromising the food safety and quality of porridge.